The effectiveness of a sentence-building treatment protocol based on Colorful Semantics: Evidence from a Greek-speaking child with Down syndrome - Papakyritsis, Ioannis; Daskalaki, Katerina; Nerantzini, Michaela (Journal of Monolingual and Bilingual Speech, 2024)
This study investigated the effectiveness of a color-coding system on the sentence-construction skills of a Greek child with Down syndrome. A five-stage single-subject design was implemented, consisting of assessment, baseline, treatment, post-treatment and follow-up phases. The treatment protocol was devised based on the Colorful Semantics program (Bryan, 2003). It focused on the construction of SVO clauses in the context of a picture-description task. The sentence-building process involved the segmentation of the target utterance into its basic syntactic constituents, facilitated by color-coding information of the subject, the verb and the object, and the use of wh- questions. Evidence based on an extensive assessment battery guided the selection and the design of the treatment program. During the baseline, post-treatment and follow-up phases, the child described the same set of action images for comparison purposes, whereas the sentence-coding protocol was introduced and implemented within two 45-minute sessions in a single week. In the baseline session, the child produced a full utterance in response only to 2/16 target pictures. After two treatment sessions, the child was able to describe almost all target pictures using full sentences, while adopting the coding system independently, without the aid of the clinician. Additionally, at 8 weeks post-treatment, the child was still able to describe nearly 50% of the pictures correctly, while using full clauses without the aid of the sentence-coding system. Conclusively, these results not only demonstrate the effectiveness of the designed treatment protocol, but also its efficiency and long-term effects. Given that the protocol was applied to a single participant, findings cannot be generalized without conducting a more extensive investigation.